EP1108 Creatsas modified vaginoplasty as stenosis vaginal treatment after pelvic radiotherapy. (1st November 2019) - Padilla-Iserte, P; Lago, V; Marina, T; Matute, L; Gurrea, M; Domingo, S
Abstract : Introduction/Background: Female sexuality is a complex phenomenon with important repercussions on their overall quality of life. In the case of women who have undergone gynecological interventions, their quality of sexual life may be diminished. Methodology: Women survivors of gynecological cancers usually have important sequelae derived from the treatment. The radicality of the surgery and / or adjuvant radiotherapy treatments are sometimes unavoidable and they involve reconstructive surgery to restore the anatomical defect (vaginal stenosis) and, in this way, the woman can recover her sexual life and body self-perception as before. Results: The role of reconstructive surgery for the anatomo-functional sequelae and body self-perception of the onco-gynecological patient has already been evaluated in previous studies (Hawighorst-Knapstein 2004, Chen 2015) with promising results since women who underwent reconstructive techniques such as Vaginoplasty with autologous peritoneal tissue (Chen 2015) improved sexual functioning and quality of life. Similar results were obtained in non-oncological patients with vaginal aplasia using the technique of vaginoplasty modified by Creatsas in which up to 95.5% of women reported feeling satisfied in their sexual life (Creatsas 2007). The surgical video is presented. With the goal of visualization this technique in the treatment of vaginal stenosis after pelvic radiotherapy for gynecological cancer. Conclusion: Reconstructive surgery such as vaginoplasty modified by Creatsas, can help to restore the anatomical defect and, ultimately, improve the patient´s body perception and quality of sexual life. Disclosure: Nothing to disclose